2005
DOI: 10.1590/s0034-71672005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação da Liderança Situacional em enfermagem de emergência

Abstract: Este trabalho foi extraído da dissertação "Liderança Situacional: um modelo para aplicação pelo enfermeiro de unidade de emergência com a equipe de enfermagem" apresentada a Escola de Enfermagem de Ribeirão Preto, RESUMOOs objetivos do estudo consistiram em identificar a correspondência de opinião entre o enfermeiro de unidade de emergência e o pessoal auxiliar de enfermagem em relação ao estilo de liderança exercido pelo enfermeiro e o estilo que este profissional deveria adotar em relação ao nível de maturid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
1
9
0
10
Order By: Relevance
“…In the emergency room, it was observed that sharing (E3) was the most common style among nurses (1) , as well as in the operating room (10) . Styles E3 and E4 were the most frequently used in the surgery hospitalization unit (11) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the emergency room, it was observed that sharing (E3) was the most common style among nurses (1) , as well as in the operating room (10) . Styles E3 and E4 were the most frequently used in the surgery hospitalization unit (11) .…”
Section: Discussionmentioning
confidence: 99%
“…In this approach, the leader's behavior in relation to subordinates in a specific task (1) is emphasized, i.e. it is founded on the interrelation b e t w e e n t h e l e a d e r 's t a s k b e h a v i o r, h i s / h e r r e l a t i o n s h i p b e h a v i o r, a n d t h e s u b o r d i n a t e s ' maturity (2) .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the style most used by nurses was E3 (sharing) while they should adopt style E4 (delegating), given the level of maturity of the auxiliary personnel, which suggests the team presented a high level of maturity (M4) (21) . A similar result was obtained in a study conducted in surgical centers in which E3 also predominated among the studied nurses.…”
mentioning
confidence: 98%
“…In this context, the analysis of literature indicated the need for a specific profile to work in the emergency sector, appointing, among other factors: clinical competency, performance, holistic care and leadership (21) ; education and professional experience, skill, physical, stress-coping, rapid decision-making, priority-setting and teamwork abilities (22) ; aptitude to obtain the patient's history, physical examination, immediate treatment, concerned with life maintenance and patients' orientation to continue treatment (23) .…”
Section: Nursing Professionals' Activities In Multiple Casualtymentioning
confidence: 99%